(untitled) (Economic and Political Thought, 2013)
Tax policy is implemented by the tax system that is in force in a particular state. The construction of taxes that create it makes it possible to implement that policy to a different extent. The article is aimed at presenting how some selected elements of the tax construction that the legislator can use do that. The subject matter of the analysis is the personal income tax. It is most susceptible to demands serving the assumed fiscal, social and economic targets. All elements of the construction can be used here but the legislator stresses some of them. They include the range of the tax, the system of tax preferences and the tax rates. As far as the range is concerned, the legislator tries to apply it to the possibly biggest number of entities so that the subjects to the tax form a big base. It is also worth highlighting that one of the most important functions of the tax is the regulation of the tax-payers’ income and wealth, and the solutions used for its construction undoubtedly influence the state of public finance and the level of fiscalism, and the functioning of a particular economy.